2004
DOI: 10.3354/meps266273
|View full text |Cite
|
Sign up to set email alerts
|

Disease and immunity in Caribbean and Indo-Pacific zooxanthellate corals

Abstract: Since the mid-1990s, coral diseases have increased in number, species affected, and geographic extent. To date, 18 coral diseases, affecting at least 150 scleractinian, gorgonian, and hydrozoan zooxanthellate species, have been described from the Caribbean and the Indo-Pacific. These diseases are associated with pathogens including bacteria, cyanobacteria, fungi, and protists and with abiotic stressors including elevated seawater temperature, sedimentation, eutrophication, and pollution. Etiologies of only 5 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
515
3
22

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(557 citation statements)
references
References 167 publications
(361 reference statements)
17
515
3
22
Order By: Relevance
“…These disease signs and epidemiological properties are consistent with those previously reported for WP (reviewed in Bythell et al, 2004;Sutherland et al, 2004;Brandt et al, 2013), and tissue loss rates were most similar to reports of WP type I disease (Dustan, 1977;Sutherland et al, 2004).…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…These disease signs and epidemiological properties are consistent with those previously reported for WP (reviewed in Bythell et al, 2004;Sutherland et al, 2004;Brandt et al, 2013), and tissue loss rates were most similar to reports of WP type I disease (Dustan, 1977;Sutherland et al, 2004).…”
Section: Methodssupporting
confidence: 79%
“…Such epizootics are of concern because they have contributed to declines in coral abundance and cover (Gardener et al, 2003;Rogers, 2009). However, of the 420 described global coral diseases, only 6-8 have pathogens ascribed to their etiology (Green and Bruckner, 2000;Sutherland et al, 2004;Rosenberg et al, 2007;Bourne et al, 2009;Pollack et al, 2011). One coral disease of particular ecological importance is white plague (WP), a rapid tissue loss disease that affects multiple species of Caribbean corals, including dominant reef-building Montastraea species.…”
Section: Introductionmentioning
confidence: 99%
“…At present, approximately 20 diseases have been identified that affect more than 100 species of corals (Sutherland et al 2004). Most diseases are caused by pathogens such as bacteria, cyanobacteria and fungi.…”
Section: Coral Diseasesmentioning
confidence: 99%
“…Most diseases are caused by pathogens such as bacteria, cyanobacteria and fungi. Pathogens can be delivered to coral reefs via terrestrial runoff (Sutherland et al 2004), or transmitted by biological vectors (Sussman et al 2003). Recent studies have highlighted the role of elevated levels of dissolved organic carbon, a common component of sewage and organic discharge, to tissue sloughing (symptomatic of many diseases) and increased coral mortality (Table 2; Kuntz et al 2005;Kline et al 2006).…”
Section: Coral Diseasesmentioning
confidence: 99%
See 1 more Smart Citation